Determination of moisture content in the Dioscorea hispida tuber using microwave method - Zainuddin, Mohamad Faiz; Abbas, Zulkifly; Muhammad Hafizi, Mardiah Hafizah; Jusoh, Mohamad Ashry; Razali, Mohd Hudzari (Faculty of Engineering, Universiti Putra Malaysia, 2012)
This study introduces an alternative method to determine percentage moisture content in a tuberous crop such as diosocorea hispida using microwave technique. Moisture content is an important parameter determining the quality of an agricultural product and their harvesting, transportation and storage processes. A microwave sensor was used in the study to penetrate deeper into the soft flesh of dioscorea hispida tuber sample. The reflection coefficient of the sensor was measured between 2 MHz and 4 GHz. The true percentage of moisture content of the sample was determined by the conventional oven drying method. The linear relationship between the conductance of the sensor and the true percentage of moisture content in the sample was determined. From the measured data, calibration equations relating conductance and percentage moisture content in the samples were established. The highest positive and negative correlations between conductance and percentage moisture content were found to be at 1.22 GHz and 3.94 GHz, respectively. The mean errors of the calibration equations at 1.22 GHz and 3.94 GHz are 10.80 and 6.95, respectively.